Integrative group psychotherapy reduces daily cortisol output and hair cortisol: A randomized active‑controlled trial with multi‑day profiling - Evgeny Pokushalov; Evgeny Terebenin; Andrey Ponomarenko; Yulia Sinyuk; Alexander Samoilov; Tatiana Gigovskaya; Marina Bubnovskaya; Dmitry Kudlay; Elena Trubicina; Claire Garcia; Richard Miller (PLoS ONE, 2026)
Background Chronic psychosocial stress can disrupt hypothalamic-pituitary-adrenal (HPA) axis and sympathetic nervous system function, yet randomized trials rarely combine multi-day diurnal salivary profiling with hair glucocorticoid assessment. Methods We conducted a parallel-group, superiority randomized controlled trial with 1:1 allocation to compare an 8-week integrative group program with a dose-matched active control. The intervention combined social-affective skills training, slow breathing with heart-rate-variability biofeedback, and cognitive reappraisal. The primary outcome was the change from baseline (T0) to end of treatment (T1) in daily salivary cortisol output, measured as the area under the curve with respect to ground (AUCg) from 3-day profiles. Key secondary outcomes were the cortisol awakening response, diurnal cortisol slope, salivary cortisone AUCg, salivary alpha-amylase AUCg, and hair cortisol concentration assessed from proximal 1-cm hair segments collected at the end of treatment and at the 6-month follow-up visit, with each segment indexing approximately the month immediately preceding collection. Outcomes were analyzed using intention-to-treat mixed-effects models with false-discovery-rate correction for secondary outcome families. Results Sixty participants were randomized to the intervention group (n = 30) or the control group (n = 30). The intervention reduced daily cortisol AUCg more than control from T0 to T1 (between-group difference in change, −21.91 nmol/L·h; 95% CI, −25.87 to −17.95), and this reduction was maintained at T2. Salivary cortisone AUCg and salivary alpha-amylase AUCg also decreased more in the intervention group. Hair cortisol concentration was lower in the proximal 1-cm segments collected at the end of treatment and at the 6-month follow-up visit. Trier Social Stress Test peak cortisol and baseline-corrected AUCi reactivity within the collected −1 to +30 min window did not differ significantly between groups. Adverse events were infrequent and similar between groups. Limitations The trial was conducted at a single site, and the Trier Social Stress Test subsample was modest. Conclusions An 8-week multicomponent group program reduced daily HPA-axis output and proximal-segment hair cortisol under active-control conditions. Trial registration ClinicalTrials.gov NCT06863948 (registered 07 Mar 2025).